2022
DOI: 10.1371/journal.pone.0263367
|View full text |Cite
|
Sign up to set email alerts
|

On mobility trends analysis of COVID–19 dissemination in Mexico City

Abstract: This work presents a tool for forecasting the spread of the new coronavirus in Mexico City, which is based on a mathematical model with a metapopulation structure that uses Bayesian statistics and is inspired by a data-driven approach. The daily mobility of people in Mexico City is mathematically represented by an origin-destination matrix using the open mobility data from Google and the Transportation Mexican Survey. This matrix is incorporated in a compartmental model. We calibrate the model against borough-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…At a global level, a positive correlation was found between human mobility and COVID-19 infections [ 45 , 92 , 75 , 76 , 139 ]. At a national scale, several studies found that mobility reduction generally implies a restrain on infections [ 59 , 140 , 141 ]. A positive correlation between mobility and excess mortality was also found in Italy [ 23 ] and Ecuador [ 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…At a global level, a positive correlation was found between human mobility and COVID-19 infections [ 45 , 92 , 75 , 76 , 139 ]. At a national scale, several studies found that mobility reduction generally implies a restrain on infections [ 59 , 140 , 141 ]. A positive correlation between mobility and excess mortality was also found in Italy [ 23 ] and Ecuador [ 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the temporary stoppage of economic and social aspects, businesses were forced to change their mindset and accelerate the onset of digitization. The active introduction of online applications allowed businesses to continue their economic activity continuously during the pandemic situation [64][65][66]. A study in Turkey investigated the impact of the pandemic on mobility and confirmed the importance of some types of mobility, such as regarding grocery stores or workplaces [67] Prediction of COVID-19 severity was evaluated in another study using longwise cluster analysis, which was evaluated as an effective way of redistributing patients based on different clinics [68].…”
Section: Discussionmentioning
confidence: 99%
“…The recent growth in the study of metapopulation dynamics has been driven partly by the COVID-19 pandemic [9][10][11][12][13][14][15][16][17] and in part by methodological advances facilitating the fitting of metapopulation models to spatiotemporal data. Until the start of this millennium, developing dynamic models with both statistical and scientific justification was a long-standing open problem for even a single population [18].…”
Section: Introductionmentioning
confidence: 99%